Urgensi Self-Efficacy Mahasiswa pada Pembelajaran Jarak Jauh - Raden Iqbal Hibatullah; Dede Nurhalizah; Sudaryat Nurdin Akhmad (Program Studi Bimbingan dan Konseling FKIP UMSU, 2022)
Self-efficacy is an important motivational variable that has been shown to have a considerable influence on a number of academic outcomes, such as an individual's interest, their task performance, and the amount of effort and persistence they are willing to expend when faced with adversity. The development of research related to self-efficacy shows that there is an urgency to continue to improve self-efficacy in the learning process. The purpose of this study was to deepen the understanding of the importance of student self-efficacy in the process or distance learning. This study uses a literature review method with data collection techniques from articles, books, and proceedings. The results of the study indicate that there is urgency in an effort to improve learning outcomes through increasing students' self-confidence that they are able to complete assignments and participate in online learning activities without feeling excessive anxiety, stress, and academic burnout. The urgency of self-efficacy in students is supported by various studies that show a positive relationship between self-efficacy and psychological aspects of students, and a negative relationship between self-efficacy and student psychological disorders.